Pengaruh jenis aktivator terhadap kadar air, kadar ph, karakteristik organoleptik, dan waktu pengomposan pupuk organik - Novia Rahayu; Fikri Maulana; Putri Dian Wulansari (Fakultas Pertanian Universitas Majalengka, 2025)
Organic fertilizer requires a relatively long decomposition time, and its final quality is greatly influenced by microbial activity during fermentation. The use of activators has been shown to accelerate composting and improve the physical and chemical properties of the resulting fertilizer. This study aims to determine the effects of different types of activators on moisture content, pH level, organoleptic properties (colour, aroma, and texture), and composting time of organic fertilizer, and to identify the most effective activator. The research employed an experimental method using a Completely Randomized Design (CRD), with four treatments control, EM4, Promi, and Caturbio, each with five replications. Data were analyzed using one-way Analysis of Variance (ANOVA), and when significant differences were found (p < 0.05), mean comparisons were performed using Duncan’s Multiple Range Test (DMRT). Organoleptic data were analyzed using the Kruskal–Wallis test followed by pairwise comparisons when applicable. The results indicated that the type of activator had a significant effect (p<0.05) on reducing moisture content and composting time, as well as significantly (p<0.05) improving aroma and texture. However, it did not significantly affect (p>0.05) the pH level or colour of the compost. The caturbio treatment yielded the best results, with the lowest moisture content (48.56 ± 4.01%), the best texture and aroma, and the fastest composting time (26.20 ± 0.83 days). The presence of microorganisms such as Azotobacter sp., Bacillus sp., Lactobacillus sp., and Trichoderma sp. in Caturbio played a key role in accelerating the decomposition of organic matter. It can be concluded that the type of activator influences the quality and efficiency of the composting process. Caturbio was found to be the most optimum activator in reducing moisture content, accelerating decomposition time, and enhancing the aroma and texture of the compost compared to the other treatments.